Persistent Hepatic Structural Alterations Following Nanoceria Vascular Infusion in the Rat. (August 2014) - Tseng, Michael T.; Fu, Qiang; Lor, Khoua; Fernandez-Botran, G. Rafael; Deng, Zhong-Bin; Graham, Uschi; Butterfield, D. Allan; Grulke, Eric A.; Yokel, Robert A.
Understanding the long-term effects and possible toxicity of nanoceria, a widely utilized commercial metal oxide, is of particular importance as it is poised for development as a therapeutic agent based on its autocatalytic redox behavior. We show here evidence of acute and subacute adverse hepatic responses, after a single infusion of an aqueous dispersion of 85 mg/kg, 30 nm nanoceria into Sprague Dawley rats. Light and electron microscopic evidence of avid uptake of nanoceria by Kupffer cells was detected as early as 1 hr after infusion. Biopersistent nanoceria stimulated cluster of differentiation 3 + lymphocyte proliferation that intermingled with nanoceria-containing Kupffer cells to form granulomata that were observed between days 30 and 90. Ultrastructural tracking of ceria nanoparticles revealed aggregated nanoceria in phagolysosomes. An increased formation of small nanoceria over time observed in the latter suggests possible dissolution and precipitation of nanoceria. However, the pathway for nanoceria metabolism/secretion remains unclear. Although frank hepatic necrosis was not observed, the retention of nanoceria increased hepatic apoptosis acutely, this persisted to day 90. These findings, together with our earlier reports of 5-nm ceria-induced liver toxicity, provide additional guidance for nanoceria development as a therapeutic agent and for its risk assessment.